A low cost solar energy converter for isolated load and/or battery charging - Toh, Yeong Hann (Nanyang Technological University, 2020)
Renewable energy is now a in demand by the world due to massive population growth and development in countries. To supply the electricity required to do these, natural resources like oil and gas have to be depleted to exchange for it. Combustion of above fossil fuels will lead to pollutions which lead to further implications like global warming and health issues to humans on long term.